THE BENEFITS OF COGNITIVE BEHAVIOR THERAPY COUNSELING TO INCREASE STUDENT RESILIENCE IN THE ERA OF SOCIETY 5.0 - Maiza Dianti, Tiara; Firman, Firman; Afdal, Afdal (Jurnal Kopendik, 2024)
This article aims to provide in-depth information about the usefulness of cognitive behavior therapy counseling to increase student resilience. In providing services to students in the era of society 5.0, guidance and counseling teachers/counselors need to pay attention to the use and procedures for implementing services using certain approaches that have proven to be effective in overcoming KES-T so that they are able to develop students' KES. The usefulness of cognitive behavior therapy counseling in increasing student resilience will be discussed in this article. This research method is a literature review where data is obtained from various reference sources such as articles, source books and other supporting documents. The research results show that cognitive behavior therapy counseling can increase student resilience and bring many benefits in developing students' KES.